2023
DOI: 10.1063/5.0129639
|View full text |Cite
|
Sign up to set email alerts
|

How are mobility and friction related in viscoelastic fluids?

Abstract: The motion of a colloidal probe in a viscoelastic fluid is described by friction or mobility, depending on whether the probe is moving with a velocity or feeling a force. While the Einstein relation describes an inverse relationship valid for Newtonian solvents, both concepts are generalized to time-dependent memory kernels in viscoelastic fluids. We theoretically and experimentally investigate their relation by considering two observables: the recoil after releasing a probe that was moved through the fluid an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…In the overdamped limit, the end of Brillouin zone is reached for ω0 γL ≈ 8, and the second term in equation ( 44 The different regimes are summarized in figure 3(c) which shows Γ as a function of ω0 /γ L for a fixed chain length N = 10 4 and different values of damping parameter γL . When ω0 ≪ γL (the overdamped limit), Γ exhibits a regime following equation (44) followed by saturation as one decreases ω0 beyond l L ≈ N. The radiation mode ( Γ = 1) is observed at the onset of the underdamped limit for γL ≪ 1 followed by the regime corresponding to the end of the Brillouin zone, where the friction coefficient is dominated by the bare friction of the driven bead, Γ = γL .…”
Section: Long Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…In the overdamped limit, the end of Brillouin zone is reached for ω0 γL ≈ 8, and the second term in equation ( 44 The different regimes are summarized in figure 3(c) which shows Γ as a function of ω0 /γ L for a fixed chain length N = 10 4 and different values of damping parameter γL . When ω0 ≪ γL (the overdamped limit), Γ exhibits a regime following equation (44) followed by saturation as one decreases ω0 beyond l L ≈ N. The radiation mode ( Γ = 1) is observed at the onset of the underdamped limit for γL ≪ 1 followed by the regime corresponding to the end of the Brillouin zone, where the friction coefficient is dominated by the bare friction of the driven bead, Γ = γL .…”
Section: Long Chainmentioning
confidence: 99%
“…In time domain, Γ of equation (50) yields Γ(t) ∼ t 3/2 and the mean square displacement (MSD) ∼ t 1/2 . We omit here a detailed translation from friction to diffusion kernel [44].…”
Section: Long Chainmentioning
confidence: 99%
“…As motion is prescribed, this description is useful in the presence of a (strong) optical trap. The connection between dynamics with trap on and trap off is non-trivial 12,13,21 , and we do not discuss it here for simplicity.…”
Section: Symmetriesmentioning
confidence: 99%
“…Therefore, pronounced memory effects (non-Markovian behavior) can be expected in such systems due to the slow relaxation of the fluid's mesoscopic microstructure and which has been confirmed using microrheological techniques [2][3][4][5][6][7][8][9] . In particular, so-called recoil experiments, where first a driving force is applied to a colloidal particle which is then suddenly removed, provide a useful method to explore how the motion of particles is modified when coupled to a slowly relaxing environment [10][11][12][13] . Previous studies have revealed rather general double-exponential recoil dynamics which can be quantitatively described by so-called bath particle models, where the response of the fluid is mimicked by harmonically coupled fictitious bath particles 12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…This fact restricts some of its applications-crucially for us it makes it impossible to describe an increasing number of regime-switching anomalous diffusion systems in which the anomalous diffusion exponent and the diffusivity change as functions of time. Examples for such phenomena include the motion of a tracer in the changing viscoelastic environment of cells during their cycle [53] or in viscoelastic solutions under pressure and/or concentration changes [54,55], in actin gels with changing mesh size [56], the motion of lipid molecules in cooling bilayer membranes [35], passive and active intracellular movement after treatment with chemicals [37,57], or intra-and inter-daily variations in the movement dynamics of larger animals [58]. Quite abrupt changes of H and/or D may be effected by binding to larger objects or surfaces [41,59] or multimerization [59,60] of the tracer.…”
Section: Introductionmentioning
confidence: 99%